Students' perspectives on clinical practice in Medical Assistant education. - Mahmud, Alias; Alwi, Nor Hayati; Sulaiman, Tajularipin; Hassan, Aminuddin (Quest Journals, 2013)
The aim of the study was to obtain student' perspectives on the clinical practice on the Diploma in Medical Assistant (DMA). The study design was cross-sectional survey performed in the Medical Assistant College, Seremban Malaysia. A self-administered questionnaire was used to 67 fourth-semester students who have undergone clinical practice in several hospitals in the state of Negeri Sembilan, Malaysia. Data were analysed descriptively as to gain the students’ perspectives in the aspects of confidence, clinical learning and the use of clinical equipment. The study outcome showed that there were a degree of concern among the students who undergo the clinical practice. Other than that, there were several issues that emerged in the clinical implementation which was the gap that exists between theory and practice such as the different equipment used in the college compared to the clinical placement where they were assigned. Practical exposure in college needs to be optimised so that it can enhance students’ confidence before they undertake clinical practice. Other than that, the implementation of theoretical teaching and practice should be integrated as to prevent the gap from forming between theory and practice.